PENGARUH PENGATURAN MODE CO DAN RPM MESIN TERHADAP EMISI GAS BUANG SEPEDA MOTOR INJEKSI - SUGENG PRAMUDIBYO PRAMUDIBYO (Polinema Press, Politeknik Negeri Malang, 2019)
The high population in Indonesia has an impact on increasing the mobility of the population in work and activities, which is followed by the increased transportation facilities needed by the community. One of the negative effects of the increasing number of vehicles is the danger of exhaust emissions. One way to minimize the danger of exhaust gases is to regulate the mixture of air and fuel on the gasoline engine. In Yamaha injection motors there is a CO setting technology, this technology will have an impact on fuel use. The standard CO on a Yamaha motorbike is 0 and can be added or reduced (±) until it reaches 30. Increasing CO one strip will cause the fuel sprayed by the injector to be reduced by 0.05 cc. Examination of exhaust gas emissions is carried out using the Qrotect 401 Engine Gas Analyzer which is capable of measuring CO2, O2, CO, HC and Lamda. Based on the test results show that the lowest exhaust emissions are produced by the vehicle at 2500 rpm and in CO-30 mode settings, namely CO gas emissions of 0.49%. So we can conclude that the lowest exhaust gas emissions are produced by the vehicle at rpm 2500 with CO-30 settings. In addition to co mode settings, variations in engine rpm also affect exhaust emissions. In different modes but with different rpm the results will also be different. In the CO 10 mode setting with rpm 1400 CO gas emission is produced at 2.102 while at 2500 rpm is produced 0.821. So at rpm 2500 produced exhaust emissions lower than rpm 1400. There is a significant effect between CO mode settings and engine rpm on motorcycle exhaust emissions.